Gioventù e adultità nella società contemporanea: riflessioni sul dibattito suscitato dai cambiamenti del corso di vita - Antonella Spanò (Quaderni di Sociologia, 2019)
The processes of social change that affected society since the 1980s had significant effects on the life course. The economic and social transformations following the exit from the “salary society” – the precariousness of work, the rise in unemployment, the lengthening of educational pathways, the welfare state’s withdrawal – made transition to adulthood a longer and more difficult process than in the past, and have also determined a significant change in the adult condition, which today can no longer be considered synonymous with stability and acquired certainties. The debate generated by the changes occurred in the social structure has highlighted the need to rethink the conceptual tools by which the phases of life are defined and interpreted. In this article the terms of the debate are resumed, with particular reference to the thesis of those who argue that, since the changes are such as to determine a radical transformation in the condition of both youth and adulthood, the transitional perspective – traditionally adopted in analyzing the passage between these two phases of life – has to be replaced with an approach capable of accounting for the processes of change, recognizing the existence of a real generational shift.